Analisis Faktor-Faktor yang Mempengaruhi Continuance Intention Pengguna Website Streaming Tidak Resmi Menggunakan Model Behavioral Acceptance - Fenilinas Adi Artanto (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the factors influencing the continuance intention of users of unlicensed film streaming websites in Indonesia. This study used a quantitative approach with a cross-sectional survey design. Data were collected through an online questionnaire from 163 respondents who had used unlicensed film streaming websites in the past six months. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS. The results showed that Convenience and Hedonic Motivation had a positive and significant effect on Satisfaction. In addition, Satisfaction, Trust, and Moral Neutralization had a positive and significant effect on Continuance Intention. Meanwhile, Perceived Risk had a negative and significant effect on Trust. However, Economic Benefit did not have a significant effect on Satisfaction, and Trust also did not have a significant effect on Satisfaction. These findings indicate that the use of unlicensed streaming websites is not only influenced by economic benefits, but also by ease of access, viewing pleasure, trust, and user moral justification. This research is expected to contribute to the development of a behavioral model for the use of illegal digital services and become a reference for official service providers in improving the quality of their services.